“How can I translate nothing into movement?”: The mimesis in Arcadia and Excuse me can you choreograph me (2022)
This article investigates different modes of correlation between word and mouvement from Luis Abraham’s (2008) concept of productive mimesis. For this purpose, we analyze two Argentine dance works that can be included in the “aesthetics of emergence” (Laddaga, 2006): Disculpe, puede usted usted coreografiarme (2007) by Laura Kalauz, and Arcadia (2017) by Bárbara Hang and Ana Laura Lozza. In both of them verbal language is used as scenic material creating images or situations which tension dance universe in different ways. We star by reviewing the concept of mimesis. Then we analyze the two pieces taking into account, firstly, how the “autopoietic loop” (Fischer-Lichte, 2011) between the performers of each piece and the spectators is established in them. Secondly, how the relationship between language and movement develops throughout the diegesis.